2009
DOI: 10.15728/bbr.2009.6.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Accounting Profit and Taxable Profit: An Analysis of Management of Accounting Results and Tax Management at Brazilian Public Companies

Abstract: This study aimed at knowing the general composition of the difference between the accounting results and tax result (book-tax differences-BTD) in Brazilian public companies in order to identify the explanation for this difference, either through the management of the earnings management (EM) and/or the taxes management (TM), or even by none of them. The research, exploratory and descriptive in nature, was based on a sample composed by the Brazilian public companies, making up a total of 276 company-years. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 15 publications
1
11
0
10
Order By: Relevance
“…This finding is in line with previous studies that have shown that BTD provide information about the earnings quality (Guenther, 2011;Tang & Firth, 2011;Tang & Firth, 2012;Hanlon, 2005;Formigoni et al, 2009;Blaylock et al, 2012). The reduced number of listed Tunisian companies on the Tunisian Stock Exchange limits the generalization of this finding.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in line with previous studies that have shown that BTD provide information about the earnings quality (Guenther, 2011;Tang & Firth, 2011;Tang & Firth, 2012;Hanlon, 2005;Formigoni et al, 2009;Blaylock et al, 2012). The reduced number of listed Tunisian companies on the Tunisian Stock Exchange limits the generalization of this finding.…”
Section: Resultssupporting
confidence: 91%
“…Further studies have used the total differences as a measure of BTD (Mills & Newberry, 2001;Lev & Nissim, 2004;Weber, 2009;Dhaliwal et al, 2009;Manzon & Plesko, 2002) (Note 4). Some other studies have analyzed the DCF through its decompositions into normal and abnormal differences (Tang & Firth, 2011;Tang & Firth, 2012;Formigoni et al, 2009). These studies have referred to Desai and Dharmapala (2006).…”
Section: Dependent Variable Measurement-abnormal Book-tax Differencesmentioning
confidence: 99%
“…A primeira causa é o desalinhamento das normas que orientam a forma de cálculo do resultado financeiro e do resultado tributário (Desai, 2005;Formigoni, Antunes & Paulo, 2009). De acordo com Plesko (2000), os relatórios fiscais e financeiros são sistemas de contabilidade separados que, embora inter-relacionados, possuem objetivos distintos.…”
Section: Book-tax Diferrencesunclassified
“…Por exemplo, os resultados da contabilidade financeira têm a finalidade de informar aos usuários os lucros que podem ser distribuídos (Hanlon, 2005;Hanlon & Heitzman, 2010), ao passo que a contabilidade tributária tem a finalidade de informar o lucro a ser tributado (Weber, 2009). As diferenças geradas por esse desalinhamento podem ser de dois tipos: permanentes e temporárias (Formigoni et al, 2009). As diferenças permanentes são originadas da diferença entre os tratamentos das normas contábeis e fiscais.…”
Section: Book-tax Diferrencesunclassified
“…Epps and Oh (1997) show that, at the announcement of the earnings of foreign companies, US investors react more when these firms are located in Anglo-Saxon countries than when these are located in continental countries (where the accounting system is used more for tax requirements). Many studies have examined this area in various countries (Aisbitt, 2002;Blake et al, 1993, Blake et al, 1997Rossignol, 1999;Rossignol, 2002;Whitaker, 2005;Nobes, 2004;Formigioni, 2009) which have different approach regarding this relationship. In continental countries, Haller (1992) and Radcliffe (1993) found that accounting is considered as an instrument of taxation which implies a strong correlation between both.…”
Section: Introductionmentioning
confidence: 99%